THE EFFECT OF TASK COMPLEXITY ON WRITING PRODUCTION - Belghoul, Hassina; Merrouche, Sarah (Journal of Human Sciences, 2020)
Task-based language teaching (TBLT) and learning is a growing area in SLA research. It has gained its rightful place in language teaching. TBLT suggests sequencing tasks from simple to complex in order to design a syllabus. However; research on the effects of task-complexity on written productions is rare. This study intends to examine the effects of manipulating task complexity along resource-directing factors and resource-dispersing ones on L2 learners' written performance. To attain this aim, we collected academic writings from 44 first year students of English at the University of Oum El Bouaghi that participated in a repeated measures experiment. The written data were measured in terms of fluency, accuracy, and complexity. A one-way ANOVA test was used for statistical analysis. We found that task complexity affects students’ writing fluency and accuracy, but it does not affect their syntactic complexity.